REVIEW: Anzac rivalries undermine Bougainville peacekeeping - Michael Field (Pacific Journalism Review, 2002)
Review of Without a Gun: Australians' Experience Monitoring Peace in Bougainville, 1997-2001, edited by Monica Wehner and Donald Denoon. Pandanus books, Australian National University.